Microfibrillar-Associated Protein 4 Regulates Stress-Induced Cardiac Remodeling. Issue 6 (3rd February 2021) - Dorn, Lisa E.; Lawrence, William; Petrosino, Jennifer M.; Xu, Xianyao; Hund, Thomas J.; Whitson, Bryan A.; Stratton, Matthew S.; Janssen, Paul M. L.; Mohler, Peter J.; Schlosser, Anders; Sorensen, Grith L.; Accornero, Federica
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Cardiac hypertrophy, a major risk factor for heart failure, occurs when cardiomyocytes remodel in response to complex signaling induced by injury or cell stress. Although cardiomyocytes are the ultimate effectors of cardiac hypertrophy, nonmyocyte populations play a large yet understudied role in determining how cardiomyocytes respond to stress. Objective: To identify novel paracrine regulators of cardiomyocyte hypertrophic remodeling. Methods and Results: We have identified a novel role for a nonmyocyte-derived and TGFβ1 (transforming growth factor β1)–induced extracellular matrix protein MFAP4 (microfibrillar-associated protein 4) in the pathophysiology of cardiac remodeling. We have determined that nonmyocyte cells are the primary sources of MFAP4 in the heart in response to TGFβ1 stimulation. Furthermore, we have demonstrated a crucial role of MFAP4 in the cardiac adaptation to stress. Global knockout of MFAP4 led to increased cardiac hypertrophy and worsened cardiac function following chronic pressure overload. Also, one week of angiotensin-mediated neurohumoral stimulation was sufficient to exacerbate cardiomyocyte hypertrophy in MFAP4 null mice. In contrast, administration of exogenous MFAP4 to isolated cardiomyocytes blunted their phenylephrine-induced hypertrophic growth through an integrin-dependent mechanism. Finally, MFAP4 deficiency leads to dysregulated integration of G protein-coupled receptor and integrin signaling in the heart. Conclusions: Altogether, our results demonstrate a critical paracrine role of MFAP4 in the development of cardiac hypertrophy and could inform future treatment options for patients with heart failure.